Alternatives to LiDAR-derived canopy height models for softwood plantations: a review and example using photogrammetry. Issue 4 (1st October 2016) - Stone, C.; Webster, M.; Osborn, J.; Iqbal, I.
ABSTRACT: Airborne LiDAR data is now commonly acquired by the Australian plantation sector in order to generate accurate digital terrain models and canopy height models at high spatial resolution for resource assessment estimates. However, these airborne surveys are relatively expensive and there is a desire to identify more affordable options for collecting or updating this information. This review presents alternative approaches to deriving canopy height models, including the use of stereo optical imagery from satellites, manned and unmanned airborne platforms, and the use of synthetic aperture radar. In addition, we illustrate the potential of airborne photogrammetry with multi-view dense point matching to produce an accurate, hybrid photo-LiDAR canopy height model at high spatial resolution along a transect covering stands of several softwood tree species.